Difficultés diagnostiques de la tuberculose cérébrale - Chahrazed Benrabah (Journal de la Faculté de Médecine d'Oran, 2022)
Abstract Tuberculosis is one of the most widespread infectious diseases in the world. It constitutes a major public health problem, especially in developing countries, including Algeria. Globally and among all tuberculosis cases, WHO reports 14% extra-pulmonary tuberculosis (EPT) without concomitant pulmonary involvement. In our country and in recent years, an upsurge in extrapulmonary tuberculosis has been observed. The objective of this article was to present an atypical case of cerebral tuberculosis whose diagnosis was late, made by anatomopathological examination with a review of the literature. We report the case of a young patient hospitalized in emergency for an intracranial hypertension syndrome with neurological disorders. Cerebral computed tomography revealed multiple brain locations with active hydrocephalus. The extension assessment was without anomaly.The patient underwent a surgical intervention, the operative consequences were favorable. The pathological examination was in favor of a specific inflammatory granulomatous lesion made up of large areas of caseous necrosis. The patient was cured under anti-tuberculosis treatment. The diagnostic problem and the results will be discussed with a review of the literature. Cerebral tuberculosis is a rare form of extrapulmonary tuberculosis. The clinic as well as the neuroimaging (CT, MRI) are atypical. The diagnosis is postoperative, based on the pathological examination. The prognosis depends on the early diagnosis, the site of the lesion and the response to anti-tuberculosis treatment.